Comparative political economy and international migration - Afonso, Alexandre (2016)
This article provides an overview of the literature connecting comparative political economy and international migration in advanced industrialised countries with a focus on the relationship between labour migration, labour markets and welfare institutions. Immigration flows and policies are considered both as independent (how migration shapes capitalist institutions) and dependent variables (how migration flows and policies are shaped by capitalist institutions). First, we discuss the impact of international migration on labour market institutions, welfare states and skill production regimes. Second, we discuss how labour market institutions and welfare arrangements shape migrant inflows and migration policies, notably via the structuration of interests of employers, organised labour and governments. We emphasise the ideas of liberalisation, segmentation, substitution and complementarity to grasp the relationship between immigration and labour market institutions.